Lead complex, precursor solution for preparing perovskite, perovskite layer, perovskite solar cell, preparation method of perovskite solar cell and application of perovskite solar cell

By introducing a one-dimensional structure lead complex PbI2·0.5La into the perovskite precursor, the problems of many microscopic holes and surface unevenness of the CsPbI3 film are solved, and the photoelectric performance and stability of the device are improved, which is of significance to guide the industrialization of perovskite solar cells.

CN119899210AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311402190.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The existing CsPbI3 perovskite films have many microscopic holes, uneven surfaces, and large defect state density, resulting in low open circuit voltage and poor stability of the device.

Method used

The one-dimensional structure lead complex PbI2·0.5La is introduced into the precursor for preparing perovskites, and the surface morphology and stability of the film are improved through its grain boundaries and surface distribution at the perovskite layer.

Benefits of technology

It improves the photoelectric performance of the device, passivates surface defects, reduces carrier recombination, improves the stability of the device, and has a guiding role in the industrialization of CsPbI3-based perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899210A_ABST
    Figure CN119899210A_ABST
Patent Text Reader

Abstract

The invention discloses a lead complex, a precursor solution for preparing perovskite, a perovskite layer, a perovskite solar cell, and a preparation method and application of the perovskite solar cell. The structural general formula of the lead complex is PbI2.0. 5La, La is a ligand, the structure of the ligand La is as follows: # imgabs0 #, R is selected from-(CH2) n-, and n is 1-8. The invention provides a novel lead complex (1D PbI2.0. 5La) aiming at the factors of more microscopic holes, uneven film, poor stability and the like of CsPbI3 perovskite, and the CsPbI3 film is prepared by introducing the 1D PbI2.0. 5La into a precursor solution for preparing the perovskite. Due to the introduction of the 1D structure, the photoelectric property of the device is improved, the surface defects are passivated, the recombination of current carriers is reduced, the stability of the device is improved, and a guiding effect on the industrialization of the CsPbI3-based perovskite solar cell is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic solar cells, and more particularly to lead complexes, precursor solutions for preparing perovskite, perovskite layers, perovskite solar cells, and preparation methods and applications thereof. Background Art

[0002] Over the past decade, the photoelectric conversion efficiency (PCE) of organic-inorganic hybrid perovskite solar cells has been improved to 25.7%.

[0003] However, the organic-inorganic hybrid perovskite contains volatile organic amine components, which affect its thermal stability to a certain extent. In addition, it is a strong acid-weak base salt and is easily decomposed under strong alkaline conditions. + , a CsPbI3 all-inorganic perovskite structure can be obtained. The CsPbI3 all-inorganic perovskite structure has attracted much attention due to its superior thermal stability and better matching energy levels when used as a series structure for silicon-based batteries.

[0004] The preparation process of CsPbI3 usually uses DMAI with a high decomposition temperature as a stabilizer to first form DMAPbI3, and then high-temperature annealing to remove DMAI. + It enters the crystal lattice to form CsPbI3. The film prepared by this method often has many microscopic holes, the film is uneven, and the defect state density is high, resulting in low open-circuit voltage and poor stability of the device.

[0005] Therefore, it is necessary to solve the problem that the existing CsPbI3 perovskite film is uneven and has many microscopic holes. Summary of the invention

[0006] In order to solve the problems in the prior art, the present invention proposes a lead complex, a precursor solution for preparing perovskite, a perovskite layer, a perovskite solar cell, a battery and a preparation method and application thereof. The present invention provides a new lead complex (1D PbI2·0.5La, wherein 1D means one-dimensional) for the CsPbI3 perovskite with many microscopic holes, uneven film, poor stability, etc., and introduces 1D PbI2·0.5La into the precursor solution for preparing perovskite to prepare CsPbI3 thin film. The introduction of 1D structure improves the photoelectric performance of the device, passivates surface defects, reduces the recombination of carriers, improves the stability of the device, and has a guiding role in the industrialization of CsPbI3-based perovskite solar cells.

[0007] One of the purposes of the present invention is to provide a lead complex, the general structural formula of the lead complex is PbI2·0.5La, wherein La is a ligand, and the structure of the ligand La is as follows:

[0008]

[0009] Wherein, R is selected from -(CH2) n -, wherein n is 1-8;

[0010] The coordination structure of the lead complex is shown below:

[0011]

[0012] In the lead complex described in the present invention, preferably,

[0013] The ligand La is selected from one of 1,2-bis([2,2'-bipyridine]-6-yloxy)ethane, 1,3-bis([2,2'-bipyridine]-6-yloxy)propane, 1,4-bis([2,2'-bipyridine]-6-yloxy)butane, 1,5-bis([2,2'-bipyridine]-6-yloxy)pentane, 1,6-bis([2,2'-bipyridine]-6-yloxy)hexane, 1,7-bis([2,2'-bipyridine]-6-yloxy)heptane and 1,8-bis([2,2'-bipyridine]-6-yloxy)octane.

[0014] The second object of the present invention is to provide a method for preparing the lead complex as described in one of the objects of the present invention, wherein the PbI2 solution and the ligand La solution are mixed and allowed to stand, and the precipitated yellow crystals are the lead complex.

[0015] In the method for preparing the lead complex of the present invention, preferably,

[0016] The PbI2 solution and the ligand La solution are optionally filtered through a filter membrane and then mixed;

[0017] The concentration of the PbI2 solution is 0.1-0.5 mmol / mL;

[0018] The concentration of the ligand La solution is 0.1-0.5 mmol / mL;

[0019] The volume ratio of the PbI2 solution to the ligand La solution is 1:1 to 1:5;

[0020] The PbI2 solution and the ligand La solution use the same solvent, which is selected from at least one of DMF, DMSO, and NMP;

[0021] The PbI2 solution and the ligand La solution are mixed and shaken rapidly for 5 to 10 seconds;

[0022] The standing time is 1 to 3 days.

[0023] In the method for preparing the lead complex of the present invention, most preferably,

[0024] Dissolve PbI2 (230.5 mg, 0.5 mmol) in 1 ml DMF and stir until completely dissolved, which is called solution A. Dissolve La (96 mg, 0.25 mmol) in 2 ml DMF and stir until completely dissolved, which is called solution B. Filter all of solution A into a 5 ml glass bottle with a 0.22 μm filter membrane, and then quickly filter all of solution B into the same bottle. Shake quickly for 5 seconds and let stand for 3 days to precipitate yellow crystals of PbI2·0.5La. Filter the obtained crystals, wash them three times with ether, and store them after drying.

[0025] The third object of the present invention is to provide a precursor solution for preparing perovskite, the precursor solution comprising PbI2, CsI, dimethylammonium hydroiodide, a lead complex and a solvent;

[0026] The lead complex is selected from the lead complex described in one of the purposes of the present invention or the lead complex prepared by the method described in the second purpose of the present invention.

[0027] In the precursor solution for preparing perovskite of the present invention, preferably,

[0028] In the precursor solution,

[0029] The concentration of PbI2 is 0.6 to 1.0 mol / L; and / or,

[0030] The concentration of CsI is 0.6 to 1.0 mol / L; and / or,

[0031] The concentration of dimethylammonium hydroiodide is 0.6 to 1.0 mol / L; and / or,

[0032] The concentration of the lead complex is 0.2-2 mg / mL; and / or,

[0033] The solvent is at least one of DMF or DMSO.

[0034] The fourth object of the present invention is to provide a perovskite layer, the perovskite layer comprising a CsPbI3 layer and a lead complex; the lead complex is distributed at the grain boundary and the surface of the CsPbI3 layer;

[0035] It is preferably prepared from the precursor solution described in the third object of the present invention.

[0036] The fifth object of the present invention is to provide a method for preparing a perovskite layer, comprising loading the precursor solution described in the third object of the present invention on a substrate and then annealing to obtain the perovskite layer;

[0037] It is preferably used for the preparation of the perovskite layer described in the fourth objective of the present invention.

[0038] In the method for preparing the perovskite layer of the present invention, preferably,

[0039] The thickness of the perovskite layer is 250-350 nm; and / or,

[0040] The loading method is spin coating; and / or,

[0041] The annealing temperature is 160 to 220° C.; and / or,

[0042] The annealing time is 10 to 60 minutes; and / or,

[0043] The volume of the precursor solution used is 30 to 100 μL; and / or,

[0044] Preferably, the spin coating speed is 2000-4000 rpm, and the time is 20-40 s.

[0045] The sixth object of the present invention is to provide a perovskite solar cell, which comprises the perovskite layer described in the fourth object of the present invention or the perovskite layer prepared by the method described in the fifth object of the present invention.

[0046] In the perovskite solar cell of the present invention, preferably,

[0047] The perovskite solar cell comprises a bottom electrode, an electron transport layer, a perovskite layer, a hole transport layer and a top electrode;

[0048] Preferably,

[0049] The bottom electrode is FTO conductive glass; and / or,

[0050] The electron transport layer is a TiO2 layer; and / or,

[0051] The hole transport layer is Spiro-OMeTAD or copper phthalocyanine; and / or,

[0052] The top electrode is gold or silver;

[0053] More preferably,

[0054] The sheet resistance of the FTO conductive glass is 5 to 30Ω, and the transmittance is 80 to 99%; and / or,

[0055] The area of ​​the bottom electrode is 1 to 9 cm 2 and / or,

[0056] The thickness of the electron transport layer is 10 to 50 nm; and / or,

[0057] The thickness of the hole transport layer is 150 to 200 nm; and / or,

[0058] The thickness of the top electrode is 50 to 150 nm.

[0059] The seventh object of the present invention is to provide a method for preparing a perovskite solar cell as described in the sixth object of the present invention, comprising the following steps:

[0060] Preparation of electron transport layer:

[0061] Spin coating the electron transport layer spin coating liquid on the bottom electrode, annealing, cooling and then plasma cleaning to obtain the bottom electrode / electron transport layer;

[0062] Preparation of perovskite layer:

[0063] Spin coating the precursor solution on the electron transport layer, and annealing to obtain a bottom electrode / electron transport layer / perovskite layer;

[0064] Preparation of hole transport layer:

[0065] Spin-coat the Spiro-OMeTAD spin-coating solution on the perovskite layer, or vacuum-evaporate copper phthalocyanine onto the perovskite layer to obtain a bottom electrode / electron transport layer / perovskite layer / hole transport layer;

[0066] Preparation of top electrode:

[0067] The bottom electrode / electron transport layer / perovskite layer / hole transport layer is subjected to vacuum evaporation treatment to prepare a top electrode, or a conductive carbon slurry is scraped on the bottom electrode / electron transport layer / perovskite layer / hole transport layer to prepare a top electrode; the perovskite solar cell is obtained.

[0068] In the method for preparing a perovskite solar cell according to the present invention, preferably,

[0069] When preparing the electron transport layer,

[0070] The spin coating liquid of the electron transport layer is a TiO2 spin coating liquid, preferably composed of: 1.5 mL ethanol or isopropanol, 15 μL concentrated hydrochloric acid, 50-150 μL tetraisopropyl titanate or tetrabutyl titanate;

[0071] During annealing, first anneal at 100-150°C for 5-30 minutes and then anneal at 450-550°C for 30-100 minutes;

[0072] The plasma cleaning treatment time is 3 to 10 minutes; and / or,

[0073] The spin coating speed is 3000-6000 rpm, and the time is 20-40 s.

[0074] In the method for preparing a perovskite solar cell according to the present invention, preferably, the Spiro-OMeTAD spin coating solution is spin coated on the perovskite layer to prepare the hole transport layer.

[0075] The hole transport layer spin coating solution contains 70-110 mg of Spiro-OMeTAD, 10-30 μL of lithium bis(trifluoromethanesulfonyl)imide solution, 10-40 μL of FK209 solution, and 20-50 μL of 4-tert-butylpyridine per milliliter of solvent; and / or,

[0076] The solvent in the hole transport layer spin coating liquid is at least one of chlorobenzene and chloroform;

[0077] Preferably, the lithium bis(trifluoromethanesulfonyl)imide solution is an acetonitrile solution with a concentration of 520 mg / mL, and the FK209 solution is an acetonitrile solution with a concentration of 300 mg / mL; and / or,

[0078] The spin coating speed is 2000-4000 rpm, and the time is 20-40 s; and / or,

[0079] When copper phthalocyanine is vacuum deposited onto the perovskite layer, the vacuum degree is less than 7×10 -4 Pa, evaporation current is 50~80A;

[0080] When preparing the top electrode, the vacuum degree of vacuum evaporation is less than 7×10 -4 Pa.

[0081] The eighth object of the present invention is to provide a perovskite solar cell as described in the sixth object of the present invention or a perovskite solar cell prepared by the method described in the seventh object of the present invention for use in photovoltaic power generation.

[0082] Compared with the prior art, the present invention has at least the following advantages:

[0083] The present invention provides a new lead complex; the present invention effectively improves the photoelectric performance of the device by introducing 1D structure PbI2·0.5La into the precursor solution for preparing perovskite, improves the surface morphology of CsPbI3 perovskite film, and enhances the overall stability.

[0084] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figure 1 is a schematic diagram of the structure of the prepared perovskite solar cell;

[0086] Figure 2 The surface electron microscope images before and after the introduction of PbI2·0.5La in Example 1 and Comparative Example 1, the left image is the surface electron microscope image of Comparative Example 1 without the addition of PbI2·0.5La, and the right image is the surface electron microscope image of Example 1 after the addition of PbI2·0.5La;

[0087] Figure 3 1 is the XRD spectrum before and after the introduction of PbI2·0.5La in the embodiment, the lower curve in the figure is the XRD spectrum of the comparative example 1 without adding PbI2·0.5La, and the upper curve in the figure is the XRD spectrum after adding PbI2·0.5La in the embodiment 1;

[0088] Figure 4 is the current-voltage test curve of the solar cell prepared in Example 1-3;

[0089] Figure 5 is a stability test curve of the perovskite solar cell prepared in Example 1;

[0090] Figure 6 This is the XRD pattern of PbI2·0.5La powder.

[0091] Description of reference numerals:

[0092] Among them, 1 is the bottom electrode, 2 is the electron transport layer, 3 is the perovskite layer, 4 is the hole transport layer, and 5 is the top electrode. DETAILED DESCRIPTION

[0093] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0094] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0095] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0096] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0097] Preparation Example 1

[0098] The ligand La is 1,3-bis([2,2'-bipyridine]-6-yloxy)propane, and its synthesis method is as follows:

[0099] Synthesis steps: Under nitrogen protection, 360 μL of 1,3-propylene glycol and 0.48 g of 60% sodium hydride were dissolved in 30 mL of anhydrous DMF and reacted at 80 ° C for 4 hours. Then 2.35 g of 6-bromo-2,2'-bipyridine was added and the reaction continued for 6 hours. After the reaction was completed, the temperature was cooled to room temperature, and a large amount of water was added to precipitate a yellow powder, which was filtered and repeatedly rinsed with water and dried. The product was purified using a silica gel column with a mobile phase of dichloromethane / ethyl acetate (V / V=10:1). Finally, the solvent was removed by rotary evaporation to obtain 1.18 g of the product with a yield of 62%.

[0100] The NMR data corresponding to 1,3-bis([2,2'-bipyridyl]-6-yloxy)propane are: 1 H NMR (CDCl3, 500MHz): 8.65 (d, J = 4.0Hz, 2H), 8.37 (d, J = 7.8Hz, 2H), 8.01 (d, J = 7.3Hz, 2H), 7.76 (t, J = 12.2, 7.8Hz, 2H), 7.70 (t, J = 12 .0,7.6Hz,2H),7.27(t,J=15.0,7.5Hz,2H),6.79(d,J=8.0Hz,2H),4.67(t,J=11.8,5.8Hz,4H),2.40(m,2H).Mass spectrum (Q-TOF) m / z[La+Na] + Theoretical value: 407.1484; measured value: 407.0619.

[0101] The above-synthesized ligand La (1,3-bis([2,2'-bipyridyl]-6-yloxy)propane) is used to prepare a lead complex, and the specific steps are as follows:

[0102] Dissolve PbI2 (230.5 mg, 0.5 mmol) in 1 ml DMF, stir until completely dissolved and record as solution A. Dissolve La (96 mg, 0.25 mmol) in 2 ml DMF, stir until completely dissolved and record as solution B. Filter all of solution A into a 5 ml glass bottle with a 0.22 μm filter membrane, and then quickly filter all of solution B into the same bottle. Shake quickly for 5 seconds and let stand for 3 days to precipitate PbI2·0.5La yellow crystals. After filtering the obtained crystals, wash them three times with ether and store them after drying. The XRD spectrum of the obtained lead complex PbI2·0.5La powder is as follows Figure 6 shown.

[0103] Preparation Example 2

[0104] The ligand La is 1,5-bis([2,2'-bipyridyl]-6-yloxy)pentane, and its synthesis method is as follows:

[0105] Synthesis steps: Under argon protection, 520 mg of 1,5-pentanediol and 0.48 g of 60% sodium hydride were dissolved in 30 mL of anhydrous DMF and reacted at 80 ° C for 4 hours. Then 2.35 g of 6-bromo-2,2'-bipyridine was added and the reaction continued for 6 hours. After the reaction was completed, the temperature was cooled to room temperature, and a large amount of water was added to precipitate a yellow powder, which was filtered and repeatedly rinsed with water and dried. The product was purified using a silica gel column with a mobile phase of dichloromethane / ethyl acetate (V / V=10:1). Finally, the solvent was removed by rotary evaporation to obtain 1.28 g of the product with a yield of 62%.

[0106] Mass spectrum (Q-TOF) corresponding to 1,5-bis([2,2'-bipyridyl]-6-yloxy)pentane m / z[La+Na] + Theoretical value: 435.1797; measured value: 435.0152.

[0107] The above-synthesized ligand La (1,5-bis([2,2'-bipyridyl]-6-yloxy)pentane) is used to prepare a lead complex, and the specific steps are as follows:

[0108] Dissolve PbI2 (230.5 mg, 0.5 mmol) in 1 ml DMF and stir until completely dissolved, which is called solution A. Dissolve La (103.5 mg, 0.25 mmol) in 3 ml DMF and stir until completely dissolved, which is called solution B. Filter all of solution A into a 5 ml glass bottle with a 0.22 μm filter membrane, and then quickly filter all of solution B into the same bottle. Shake quickly for 10 seconds and let stand for 1 day to precipitate yellow crystals of PbI2·0.5La. Filter the obtained crystals, wash them three times with ether, and store them after drying.

[0109] Preparation Example 3

[0110] The ligand La is 1,8-bis([2,2'-bipyridine]-6-yloxy)octane, and its synthesis method is as follows:

[0111] Synthesis steps: Under argon protection, 725 mg of 1,8-octanediol and 0.48 g of 60% sodium hydride were dissolved in 30 mL of anhydrous DMF and reacted at 80 ° C for 4 hours. Then 2.35 g of 6-bromo-2,2'-bipyridine was added and the reaction continued for 6 hours. After the reaction was completed, the temperature was cooled to room temperature, and a large amount of water was added to precipitate a yellow powder, which was filtered and repeatedly rinsed with water and dried. The product was purified using a silica gel column with a mobile phase of dichloromethane / ethyl acetate (V / V=10:1). Finally, the solvent was removed by rotary evaporation to obtain 1.25 g of the product with a yield of 55%.

[0112] Mass spectrum (Q-TOF) corresponding to 1,8-bis([2,2'-bipyridyl]-6-yloxy)octane m / z[La+Na] + Theoretical value: 477.2266; measured value: 477.0148.

[0113] The above-synthesized ligand La (1,8-bis([2,2'-bipyridine]-6-yloxy)octane) is used to prepare a lead complex, and the specific steps are as follows:

[0114] Dissolve PbI2 (230.5 mg, 0.5 mmol) in 1 ml DMF and stir until completely dissolved, which is called solution A. Dissolve La (113.5 mg, 0.25 mmol) in 5 ml DMF and stir until completely dissolved, which is called solution B. Filter all of solution A into a 10 ml glass bottle with a 0.22 μm filter membrane, and then quickly filter all of solution B into the same bottle. Shake quickly for 10 seconds and let stand for 2 days to precipitate yellow crystals of PbI2·0.5La. Filter the obtained crystals, wash them three times with ether, and store them after drying.

[0115] Example 1

[0116] Step (1) Cleaning of conductive glass:

[0117] The substrate was ultrasonically treated with detergent, deionized water, acetone, and isopropanol for 20 min, then dried with a hair dryer, and then treated with a plasma cleaner for 3 min;

[0118] Step (2) Preparation of electron transport layer:

[0119] 100 μL of tetraisopropyl titanate and 15 μL of concentrated hydrochloric acid were added to 1.5 mL of ethanol and stirred for 30 min, and then spin-coated on the substrate in step (1) at a speed of 5000 rpm for 30 s using a sizing machine to obtain a TiO2 layer. The TiO2 layer was annealed at 120°C for 10 min to remove the solvent, and then heated to 500°C for 40 min. After cooling, the layer was treated with a plasma cleaner for 3 min.

[0120] Step (3) Preparation of perovskite layer:

[0121] The prepared perovskite spin coating liquid was spin-coated on the substrate on which TiO2 was deposited in (2) at a speed of 3000 rpm through a spun coating machine for 30 seconds, and annealed to obtain a 3D perovskite layer of about 300 nm thick. The annealing temperature was 180°C and the time was 8 minutes.

[0122] The precursor solution is composed of 0.7M PbI2, 0.7M CsI, 0.7M dimethylammonium hydroiodide (DMAI) and 1mg / mL PbI2·0.5La (the lead complex prepared in Preparation Example 1); the volume of the precursor solution used is 60μL;

[0123] Step (4) Preparation of hole transport layer:

[0124] Spin-coat the prepared Spiro-OMeTAD solution on the surface of the perovskite film prepared in step (3) to obtain a hole transport layer with a thickness of about 180 nm, wherein the volume of the Spiro-OMeTAD solution is 30 μL, the rotation speed is 3000 rpm, and the time is 30 s;

[0125] The solvent of the hole transport layer spin coating liquid is chlorobenzene, and each milliliter of chlorobenzene contains 72.3 mg of Spiro-OMeTAD, 17.5 μL of lithium bis(trifluoromethanesulfonyl imide), 29 μL of FK209 (tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridinium)cobalt(III)tris[bis(trifluoromethane)sulfonyl imide]), and 28.8 μL of 4-tert-butylpyridine;

[0126] Among the above additives, lithium bistrifluoromethanesulfonyl imide is an acetonitrile solution with a concentration of 520 mg / mL, and FK209 is an acetonitrile solution with a concentration of 300 mg / mL.

[0127] Step (5) Preparation of metal top electrode:

[0128] The prepared substrate was placed in a vacuum evaporation device and silver particles were added. The vacuum degree was less than 7×10 -4 Pa, the evaporation rate is controlled at The thickness of the silver electrode is about 100 nm. The prepared perovskite solar cell is recorded as 3D / 1D / Spiro. The test results of the prepared battery performance are shown in Table 1.

[0129] The schematic diagram of the battery structure prepared in the above embodiment is as follows Figure 1 As shown. It includes a bottom electrode 1 (here conductive FTO), an electron transport layer 2 (here TiO2 electron transport layer), a perovskite layer 3, a hole transport layer 4 (here Spiro-OMeTAD hole transport layer), and a top electrode 5 (here silver electrode).

[0130] Comparative Example 1

[0131] The preparation method is basically the same as that in Example 1, except that:

[0132] In step (3), when preparing the perovskite layer, PbI2·0.5La is not added. The prepared perovskite solar cell is denoted as 3D / Spiro. The test results of the prepared cell performance are shown in Table 1.

[0133] Comparative Example 2

[0134] The preparation method is basically the same as that in Example 1, except that:

[0135] Without preparing the Spiro-OMeTAD hole transport layer, the conductive carbon is directly coated on the surface of the perovskite film prepared in step (3) by scraping, and annealed at 100°C for 10 minutes. A carbon-based CsPbI3 perovskite device without HTM (Spiro-OMeTAD hole transport layer) is obtained. The prepared perovskite solar cell is recorded as 3D / 1D / C. The test results of the prepared battery performance are shown in Table 1.

[0136] Example 2

[0137] The preparation method is basically the same as that in Example 1, except that:

[0138] Copper phthalocyanine is deposited on the surface of the perovskite film prepared in step (3) by vacuum evaporation at a deposition rate of A hole transport layer with a thickness of 30 to 60 nm is obtained.

[0139] Conductive carbon was coated on the surface of the perovskite film prepared in step (3) by scraping, and annealed at 100° C. for 10 min. The prepared perovskite solar cell was recorded as 3D / 1D / CuPc / C. The test results of the prepared cell performance are shown in Table 1.

[0140] Example 3

[0141] The preparation method is basically the same as that in Example 1, except that:

[0142] The PbI2·0.5La used is the lead complex prepared in Preparation Example 2. The test results of the prepared battery performance are shown in Table 1.

[0143] Example 4

[0144] The preparation method is substantially the same as that of Example 1, except that the PbI2·0.5La used is the lead complex prepared in Preparation Example 3. The test results of the prepared battery performance are shown in Table 1.

[0145] The test results of the battery performance of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention are as follows: Figure 4 And as shown in Table 1.

[0146] Table 1

[0147]

[0148] By comparing the results of Example 1 and Comparative Example 1, it can be seen that the method of introducing 1D PbI2·0.5La into the perovskite precursor solution improves the CsPbI3 thin film. The introduction of the 1D structure improves the photoelectric performance of the device, passivates surface defects, reduces the recombination of carriers, and improves the stability of the device. In addition, the present invention Figure 2 The surface electron microscopy images before and after the introduction of PbI2·0.5La also show that the surface defects of the CsPbI3 film are passivated after the introduction of 1D PbI2·0.5La; Figure 3 The XRD patterns before and after the introduction of PbI2·0.5La also show that a small number of DMAPbI3 peaks can be observed in the spectrum of 1D PbI2·0.5La before addition, indicating that DMAI is not completely removed. After addition, the peak disappears, and the peak of 1D PbI2·0.5La can be observed. Therefore, the introduction of 1D structure PbI2·0.5La in the present invention effectively improves the photoelectric performance of the device, improves the surface morphology, and enhances the overall stability.

[0149] By comparing the results of Example 1, Comparative Example 1 and Comparative Example 2, the battery performance of the 3D / 1D / Spiro battery prepared in Example 1 is significantly higher than that of the undoped PbI2·0.5La based device.

[0150] In addition, the stability test curve of the perovskite solar cell prepared in Example 1 is as follows Figure 5 As shown, Figure 5In the figure, the control group refers to the perovskite solar cell prepared in comparative example 1. As can be seen from the figure, the method of introducing 1D PbI2·0.5La into the precursor solution for preparing perovskite is used to prepare CsPbI3 thin film. The introduction of 1D structure improves the photoelectric performance of the device, passivates surface defects, reduces the recombination of carriers, improves the stability of the device, and plays a guiding role in the industrialization of CsPbI3-based perovskite solar cells.

[0151] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0152] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0153] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0154] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A lead complex, characterized in that: The general structural formula of the lead complex is PbI2·0.5La, wherein La is a ligand, and the structure of the ligand La is as follows: Wherein, R is selected from -(CH2) n -, wherein n is 1-8; The coordination structure of the lead complex is shown below:

2. The lead complex according to claim 1, characterized in that: The ligand La is selected from one of 1,2-bis([2,2'-bipyridine]-6-yloxy)ethane, 1,3-bis([2,2'-bipyridine]-6-yloxy)propane, 1,4-bis([2,2'-bipyridine]-6-yloxy)butane, 1,5-bis([2,2'-bipyridine]-6-yloxy)pentane, 1,6-bis([2,2'-bipyridine]-6-yloxy)hexane, 1,7-bis([2,2'-bipyridine]-6-yloxy)heptane and 1,8-bis([2,2'-bipyridine]-6-yloxy)octane.

3. A method for preparing the lead complex according to any one of claims 1 to 2, characterized in that: The PbI2 solution and the ligand La solution are mixed and allowed to stand, and the precipitated yellow crystals are the lead complex.

4. The method for preparing the lead complex according to claim 3, characterized in that: The PbI2 solution and the ligand La solution are optionally filtered through a filter membrane and then mixed; The concentration of the PbI2 solution is 0.1-0.5 mmol / mL; The concentration of the ligand La solution is 0.1-0.5 mmol / mL; The volume ratio of the PbI2 solution to the ligand La solution is 1:1 to 1:5; The PbI2 solution and the ligand La solution use the same solvent, which is selected from at least one of DMF, DMSO, and NMP; The PbI2 solution and the ligand La solution are mixed and shaken rapidly for 5 to 10 seconds; The standing time is 1 to 3 days.

5. A precursor solution for preparing perovskite, characterized in that: The precursor solution comprises PbI2, CsI, dimethylammonium hydroiodide, a lead complex and a solvent; The lead complex is selected from the lead complex described in any one of claims 1-2 or the lead complex prepared by the method described in any one of claims 3-4.

6. The precursor solution for preparing perovskite according to claim 5, characterized in that: In the precursor solution, The concentration of PbI2 is 0.6 to 1.0 mol / L; and / or, The concentration of CsI is 0.6 to 1.0 mol / L; and / or, The concentration of dimethylammonium hydroiodide is 0.6 to 1.0 mol / L; and / or, The concentration of the lead complex is 0.2-2 mg / mL; and / or, The solvent is at least one of DMF or DMSO.

7. A perovskite layer, characterized in that: The perovskite layer includes a CsPbI3 layer and a lead complex; the lead complex is distributed at the grain boundary and the surface of the CsPbI3 layer; Preferably, it is prepared from the precursor solution described in any one of claims 5-6.

8. A method for preparing a perovskite layer, characterized in that: The perovskite layer is obtained by loading the precursor solution according to any one of claims 5 to 6 on a substrate and then annealing the substrate; It is preferably used for preparing the perovskite layer according to claim 7.

9. The method for preparing a perovskite layer according to claim 8, characterized in that: The thickness of the perovskite layer is 250-350 nm; and / or, The loading method is spin coating; and / or, The annealing temperature is 160 to 220° C.; and / or, The annealing time is 10 to 60 minutes; and / or, The volume of the precursor solution used is 30 to 100 μL; and / or, Preferably, the spin coating speed is 2000-4000 rpm, and the time is 20-40 s.

10. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the perovskite layer according to claim 7 or the perovskite layer prepared by the method according to any one of claims 8 to 9.

11. The perovskite solar cell according to claim 10, characterized in that: The perovskite solar cell comprises a bottom electrode, an electron transport layer, a perovskite layer, a hole transport layer and a top electrode; Preferably, The bottom electrode is FTO conductive glass; and / or, The electron transport layer is a TiO2 layer; and / or, The hole transport layer is Spiro-OMeTAD or copper phthalocyanine; and / or, The top electrode is gold or silver; More preferably, The sheet resistance of the FTO conductive glass is 5 to 30Ω, and the transmittance is 80 to 99%; and / or, The area of ​​the bottom electrode is 1 to 9 cm 2 and / or, The thickness of the electron transport layer is 10 to 50 nm; and / or, The thickness of the hole transport layer is 150 to 200 nm; and / or, The thickness of the top electrode is 50 to 150 nm.

12. A method for preparing a perovskite solar cell according to any one of claims 10 to 11, characterized in that: The following steps are involved: Preparation of electron transport layer: Spin coating the electron transport layer spin coating liquid on the bottom electrode, annealing, cooling and then plasma cleaning to obtain the bottom electrode / electron transport layer; Preparation of perovskite layer: Spin coating the precursor solution on the electron transport layer, and annealing to obtain a bottom electrode / electron transport layer / perovskite layer; Preparation of hole transport layer: Spin-coat the Spiro-OMeTAD spin-coating solution on the perovskite layer, or vacuum-evaporate copper phthalocyanine onto the perovskite layer to obtain a bottom electrode / electron transport layer / perovskite layer / hole transport layer; Preparation of top electrode: The bottom electrode / electron transport layer / perovskite layer / hole transport layer is subjected to vacuum evaporation treatment to prepare a top electrode, or a conductive carbon slurry is scraped on the bottom electrode / electron transport layer / perovskite layer / hole transport layer to prepare a top electrode; the perovskite solar cell is obtained.

13. The method for preparing a perovskite solar cell according to claim 12, characterized in that: When preparing the electron transport layer, The spin coating liquid of the electron transport layer is TiO2 spin coating liquid; During annealing, first anneal at 100-150°C for 5-30 minutes and then anneal at 450-550°C for 30-100 minutes; The plasma cleaning treatment time is 3 to 10 minutes; and / or, The spin coating speed is 3000-6000 rpm, and the time is 20-40 s.

14. The method for preparing a perovskite solar cell according to claim 12, characterized in that: The Spiro-OMeTAD spin coating solution is spin-coated on the perovskite layer to prepare the hole transport layer. The hole transport layer spin coating solution contains 70-110 mg of Spiro-OMeTAD, 10-30 μL of lithium bis(trifluoromethanesulfonyl)imide solution, 10-40 μL of FK209 solution, and 20-50 μL of 4-tert-butylpyridine per milliliter of solvent; and / or, The solvent in the hole transport layer spin coating liquid is at least one of chlorobenzene and chloroform; Preferably, the lithium bis(trifluoromethanesulfonyl)imide solution is an acetonitrile solution with a concentration of 520 mg / mL, and the FK209 solution is an acetonitrile solution with a concentration of 300 mg / mL; and / or, The spin coating speed is 2000-4000 rpm, and the time is 20-40 s; and / or, When copper phthalocyanine is vacuum deposited onto the perovskite layer, the vacuum degree is less than 7×10 -4 Pa, evaporation current is 50~80A; When preparing the top electrode, the vacuum degree of vacuum evaporation is less than 7×10 -4 Pa.

15. Use of the perovskite solar cell according to any one of claims 10 to 11 or the perovskite solar cell prepared by the method according to any one of claims 12 to 14 in photovoltaic power generation.

Citation Information

Patent Citations

  • Method for preparing phosphorus-containing ligands

    CN114891036A

  • Interface modification electron transport layer, perovskite solar cell and preparation method of perovskite solar cell

    CN116847666A